2020
DOI: 10.4269/ajtmh.20-0780
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Clinical Course of Patients with Scrub Typhus and Queensland Tick Typhus Infection Requiring Intensive Care Unit Admission: A 23-year Case Series from Queensland, Tropical Australia

Abstract: Scrub typhus and Queensland tick typhus (QTT)-rickettsial infections endemic to tropical Australia-can cause life-threatening disease. This retrospective study examined the clinical course of all patients with laboratoryconfirmed scrub typhus or QTT admitted to the intensive care unit (ICU) of a tertiary referral hospital in tropical Australia between 1997 and 2019. Of the 22 patients, 13 had scrub typhus and nine had QTT. The patients' median (interquartile range [IQR]) age was 50 (38-67) years; 14/22 (64%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The study only reflects clinical management strategies used at this center which evolved significantly over the study period. 11,12 There were only 21 cases with rickettsial disease, and this group included patients with both scrub typhus and QTT, conditions caused by different pathogens. Some rickettsiologists may take issue with this approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study only reflects clinical management strategies used at this center which evolved significantly over the study period. 11,12 There were only 21 cases with rickettsial disease, and this group included patients with both scrub typhus and QTT, conditions caused by different pathogens. Some rickettsiologists may take issue with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…31 Rickettsial infection was diagnosed if there was a clinical diagnosis of O. tsutsugamushi or R. australis infection accompanied by a positive polymerase chain reaction (PCR), a 4-fold rise in titers of paired serological samples (confirmed infection) or a single serological titer $128 with a clinically compatible syndrome (two or more of fever, rash, eschar, myalgia, or headache with no convincing alternative diagnosis) (probable infection). 12 Demographic, clinical, and laboratory data were collected from electronic and paper medical records. The study's primary endpoint was death before ICU discharge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple organ dysfunction syndromes (MODS) are reported frequently (34–50%) in patients with rickettsial infections, and 18 to 30% of these patients require ventilatory support. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that delays in the recognition and administration of appropriate antibiotic therapy increase the chance of severe disease, whereas early diagnosis and appropriate management of complications improve outcomes. 5 7 Hence, in order to reduce morbidity and mortality due to rickettsial infections, there needs to be a high clinical suspicion of these infections in the presence of epidemiological data and clinical manifestations, such as rash, eschar, and multi-organ involvement. Further, laboratory clues, such as elevated liver enzymes, thrombocytopenia, and normal or mildly elevated white blood counts, should prompt the diagnosis of rickettsial infections, and appropriate treatment needs to be initiated as soon as possible.…”
Section: Introductionmentioning
confidence: 99%